Oncological benefits of postoperative radiotherapy in node-negative early stage cancer of the oral cavity with isolated perineural invasion. Issue 5 (June 2019) - Rajappa, S.K.; Ram, D.; Shukla, H.; Mandal, G.; Venkatasubramaniyan, M.; Dubey, A.; Agarwal, M.; Kumar, R.; Dewan, A.K.
Abstract: Perineural invasion has been widely regarded as a poor prognostic factor in cancer of the oral cavity, but adjuvant treatment based only on this is still debatable. We have made an effort to address the question in a retrospective analysis of data from 2009–15 of patients with early node-negative cancers of the oral cavity. Patients with perineural invasion were divided into those who were treated with radiotherapy and those who were not. The records of a total of 169 patients were analysed, and 118 were given adjuvant radiotherapy and 51 were not. The median (range) duration of follow up was 45 (26–86) months. Of 169 patients, 47 (28%) developed recurrence, 28 in the treated, and 19 in the untreated, group. There was a significant disease-free survival benefit for adjuvant treatment (p = 0.047) but no overall survival benefit (p = 0.54). We conclude that adjuvant radiotherapy should be considered for patients with perineural invasion, even in early cancers of the oral cavity.